Pengaruh Pemberian Kompres Hangat terhadap Penurunan Intensitas Nyeri Persalinan pada Ibu Inpartu Kala I Fase Aktif - Irawati, Irawati; Muliani, Muliani; Arsyad, Gusman (Poltekkes Kemenkes Palu, 2019)
Pain is a body protection mechanism that arises when the tissue is damaged and causes the individual reaction to relieve pain. Related to discomfort and pain, therefore, researchers want to apply warm compress techniques to reduce pain in labor. This study aims to determine the effect of giving warm compresses to the decrease in the intensity of pain in mothers in labor during the active phase. The method used is Pre-experiment with one group pretest-posttest design. The population in this study were all primigravida maternal mothers in the Puskesmasn Kampung Baru with a sample of 15 respondents selected by consecutive sampling. The statistical test used was the Wilcoxon Rant Test. The results of this study were the mean value before a warm compress performed 7.6, and the mean value after a warm compress was 5.8, with a significance value of 0.001. This study concludes that there is an effect of giving warm compresses to the decrease in labor pain in the first-phase mother of the active phase. By giving warm compresses, the responsiveness feels more relaxed so that the psychological state does not focus on the pain she feels. The results of this study are expected to be applied in health facilities such as hospitals, maternity clinics, and health centers.